IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Abdullah, Darda; Faijah Kurniati, Denia (STKIP Subang, 2019)
This research was motivated by the observation in the fourth grade SD Assalaam Bandung, which showed the students do not understand the material presented by educators and educators still use the conventional method of the lectures, the learning process is only centered on the teacher and without involving students so less anttractive and low student learning outcomes ,and this reseach aims to improve student learning outcomes in the theme of togetherness and diversity in class IV SD Assalaam Bandung. Therefore research are trying to improve student learning outcomes by applying the problem based learning (PBL). Research methodology study conducted oy research in the form of classroom action research (PTK), for  research conducted in accordance duites and function of the teacher when implementing the learning in the classroom. With the aims to reflect and to improve the learning process so that their learning outcome. Subjects in the study were students of class IVB SD Assalaam Bandung with the number 20 students consisting of 14 boys and 6 girls. This study was conducted 3 cycles where each cycle consisted of two learning. The research results by using the model of  Problem Based Learning (PBL) in the first cycle of student learning outcomes with a percentage of 26,6%, second cycle 46,6%, and cycle III 86,6%. While for the implementation of learning cycle I 60%, cycle II 76,25%, and cycle III 82,5%. The learning outcomes consist of cognitive, affective and psychomotor domains. The cognitive domain obtained the percentage of the first cycle reached 20%, the second cycle reached 30% and the third cycle reached 80%. While the affective domain of the first cycle reached 30%, the second cycle 70%, and the third cycle 90% and for the psychomotor domain the first cycle 30%, the second cycle 40%, and the third cycle 90%. Based on the results of the study it can be concluded that the application of the Problem Based Learning (PBL) model can improve student learning outcomes in the togetherness sub-theme in class IV SD Assalaam Bandung.